2013
DOI: 10.1073/pnas.1217611110
|View full text |Cite
|
Sign up to set email alerts
|

Membrane lipid saturation activates endoplasmic reticulum unfolded protein response transducers through their transmembrane domains

Abstract: Endoplasmic reticulum (ER) stress sensors use a related luminal domain to monitor the unfolded protein load and convey the signal to downstream effectors, signaling an unfolded protein response (UPR) that maintains compartment-specific protein folding homeostasis. Surprisingly, perturbation of cellular lipid composition also activates the UPR, with important consequences in obesity and diabetes. However, it is unclear if direct sensing of the lipid perturbation contributes to UPR activation. We found that muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
568
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(632 citation statements)
references
References 45 publications
36
568
2
3
Order By: Relevance
“…For example, perturbation of the lipid bilayer of the ER by the expression of a tail-anchored ER membrane protein resulted in the selective activation of ATF6, in the absence of IRE1␣ and PERK activation (and without ER Ca 2ϩ depletion) (42). Conversely, a recent study has demonstrated that saturation of membrane lipids promoted selective IRE1␣ and PERK activation by enhancing dimerization via their transmembrane domains (43). Defining the precise mechanism of ATF6 activation by iPLA 2 ␥ will require further investigation.…”
Section: Table 3 Effect Of Ipla 2 ␥ On Ldlr Promoter-luciferase Repormentioning
confidence: 99%
“…For example, perturbation of the lipid bilayer of the ER by the expression of a tail-anchored ER membrane protein resulted in the selective activation of ATF6, in the absence of IRE1␣ and PERK activation (and without ER Ca 2ϩ depletion) (42). Conversely, a recent study has demonstrated that saturation of membrane lipids promoted selective IRE1␣ and PERK activation by enhancing dimerization via their transmembrane domains (43). Defining the precise mechanism of ATF6 activation by iPLA 2 ␥ will require further investigation.…”
Section: Table 3 Effect Of Ipla 2 ␥ On Ldlr Promoter-luciferase Repormentioning
confidence: 99%
“…In yeast, inositol depletion can trigger UPR activation in the absence of significant changes in the ER misfolded protein burden [62]. The ability of membrane lipid perturbations to induce UPR independently of accumulation of misfolded proteins has been described using genetic and biochemical methods in both yeast and mammalian cells [25, 83]. Therefore, changes in BiP/Kar2 mobility, when coupled to other biochemical analysis, can directly assess changes in the misfolded protein burden in living cells.…”
Section: Approaches For Imaging Er Stress and Upr Activity In Livinmentioning
confidence: 99%
“…27 It is also noteworthy, that the lipid composition of the ER membrane has been reported to contribute to the unfolded protein response. 28 We have shown that rock1 mutant plants are characterized by a strongly increased size and activity of the inflorescence meristem, indicating a negative regulatory role of ROCK1 in shoot meristem development. Elevated levels of endogenous cytokinins and cytokinin response genes in rock1 inflorescences suggest that ROCK1 regulates the cytokinin activity in meristematic cells.…”
Section: Biological Function Of Rock1 Transport Activitymentioning
confidence: 99%